2022
DOI: 10.1021/acsami.2c14045
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Mn-Doped N-Rich Carbon Dots with Tunable Photoluminescence and Oxidase-Mimetic Activity Enabling Bimodal Ratiometric Colorimetric/Fluorometric Detection of Nitrite

Abstract: Multimodal detection is a promising paradigm because of its advantages of expanding usage scenarios and improving reliability. However, it is very challenging to design reasonable strategies to achieve the multimodal sensing of targets. Herein, we developed an unprecedented bimodal ratiometric colorimetric/fluorometric method by exploring a novel bifunctional artificial oxidase mimic, Mn-doped N-rich carbon dots (Mn-CDs), to achieve the high-performance determination of nitrite in complicated matrices. The Mn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Due to the presence of aromatic primary amines in TMBox, a diazotization reaction occurs between TMBox and nitrite under an acid environment (pH 3.5). AA can reduce the semi-quinone-imine structure in the diazotized TMBox to the aromatic hydrocarbon amino group structure, but it cannot reduce the diazo structure, as shown in Figure D. Therefore, the remaining peak at 445 nm may be the product of diazotized TMB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of aromatic primary amines in TMBox, a diazotization reaction occurs between TMBox and nitrite under an acid environment (pH 3.5). AA can reduce the semi-quinone-imine structure in the diazotized TMBox to the aromatic hydrocarbon amino group structure, but it cannot reduce the diazo structure, as shown in Figure D. Therefore, the remaining peak at 445 nm may be the product of diazotized TMB.…”
Section: Resultsmentioning
confidence: 99%
“…These two cases indicated that the peak at 445 nm was not completely reduced after the addition of AA, which may suggest that the overoxidized TMBox at this peak was reduced to colorless TMB. However, the remaining peak may be ascribed to the product of the diazotization reaction . In addition to using AA, 1-naphthylamine was also utilized for validation which was considered as a characteristic reaction for the diazotization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…18 For instance, an unprecedented bimodal ratiometric colorimetric/fluorometric method by exploring a novel bifunctional artificial oxidase mimic was developed based on Mn-doped N-rich carbon dots (Mn-CDs) for achieving the high-performance determination of nitrite in complicated matrices. 19 Consequently, how to rationally construct the sensing platform to realize the dualsignal response of NO 2 − is a great challenge. Nanomaterials with oxidase-like catalytic behavior (enzyme mimics) have obtained much research interest in recent years, which display the superb performance of low cost, outstanding stability, and excellent catalytic activity.…”
Section: Nitrite (Nomentioning
confidence: 99%
“…Ratiometric colorimetric probes have self-calibration behavior to enhance the reliability, sensitivity, and selectivity of monitoring in relatively complex matrices and further avoid false positive . For instance, an unprecedented bimodal ratiometric colorimetric/fluorometric method by exploring a novel bifunctional artificial oxidase mimic was developed based on Mn-doped N-rich carbon dots (Mn-CDs) for achieving the high-performance determination of nitrite in complicated matrices . Consequently, how to rationally construct the sensing platform to realize the dual-signal response of NO 2 – is a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…23 The incorporation of transition metals such as Fe, Cu, or Mn into CDs has been reported to create highly active nanozymes with peroxidase-like and oxidase-like activities. [24][25][26][27] Most of the existing synthetic routes for metaldoped CDs use randomly combined organic molecules and metal ions as precursors, resulting in low yields. The lack of indepth understanding of organic-metal interactions also leads to almost irreproducible synthesis of metal-doped CDs and difficulty in precise doping.…”
Section: Introductionmentioning
confidence: 99%